A Prospective Observational Study to Assess Rationality and Drug Characterisation in the Prescription of Opioids in Post-Operative Patients in A Tertiary Care Hospital - S, Satish; Firdous, Fathima; Shabaraya, A.R (Asian Journal of Pharmaceutical Research and Development, 2025)
Opioid are the narcotic analgesics which are routinely prescribed for postoperative pain management.The CDC developed guidelines for prescribing opioids to ensure safe, effective care and reduce opioid-related issues in chronic pain management. This prospective observational study focused on assessment of rationality opioid in the prescription and drug characterization of opioid among post operative patients in a tertiary care hospital for a period of 6 months. The data was collected using information provided by patient medical record, CDC guidelines were used to assess rationality. Rationality in the opioid prescription was assessed using CDC guideline and revealed that majority of the opioid prescription were rational. High degree of irrationality was observed with Inj.Tramadol and long duration opioid prescription, emphasizing the importance of implementation of CDC guidelines. Opioid drug characterization study revealed that majority of the patients were prescribed with Tab. Tramadol during hospitalization and discharge followed by inj. Tramadol, buprenorphine, morphine. In addition, some of the patients prescribed with buprenorphine at discharge possibly indicating leading to the misuse of the opioid.